Dwie rozmowy o Józefie Wittlinie - Wielgosz, Ewa (Tematy i Konteksty, 2015)
The leitmotivs of the interviews held with Elżbieta Wittlin Lipton are both the life and the artistic work of her father Józef Wittlin, the author of Sól ziemi. This fact makes the interviews more personal, because less-well-known facts and concealment are revealed, distortions are clarified and inaccuracies concerning the writer’s biography are accounted for. The first interview was recorded in March 2013 in Elżbieta Wittlin Lipton’s house in Madrid. The subject matter focused on Wittlin’s interests, sources of inspiration and friendships. In turn, the second interview was recorded in May 2014 in Rzeszów, and was a kind of reconstruction/quest of her father’s traces. These memories, or wayfarings, made by Wittlin’s daughter enable us to create a portrait of her father and outline the reception of his works. In this sense, the interview proves the reviving presence of the author of Mój Lwów in his motherland.